2023
DOI: 10.1039/d2cc05963k
|View full text |Cite
|
Sign up to set email alerts
|

The emerging chemistry of the aluminyl anion

Abstract: The chemistry of low valent p-block metal complexes continues to elicit interest in the research community, demonstrating reactivity that replicates and in some cases exceeds that of their more widely...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 111 publications
0
51
0
2
Order By: Relevance
“…We have previously described the impact on the reactivity of the Cu–Al bond induced through variation of the copper-coordinated carbene ligand and the differentiated behaviour observed across the metals of the group 11 triad. 13 To investigate the generality of the transformations observed to provide compounds 2 and 3 , therefore, phenylacetylene was reacted with further compounds comprising unsupported group 11–Al{SiN Dipp } bonds. In stark contrast to the exclusive production of 2 , treatment of [( Me2 CAAC)CuAl{SiN Dipp }] ( 4 ), containing the more basic Me2 CAAC carbene ( Me2 CAAC = 1-(2,6-di-isopropylphenyl)-3,3,5,5-tetramethylpyrrolidin-2-ylidene), with phenylacetylene provided a mixture of several products, even at room temperature and irrespective of the reaction stoichiometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously described the impact on the reactivity of the Cu–Al bond induced through variation of the copper-coordinated carbene ligand and the differentiated behaviour observed across the metals of the group 11 triad. 13 To investigate the generality of the transformations observed to provide compounds 2 and 3 , therefore, phenylacetylene was reacted with further compounds comprising unsupported group 11–Al{SiN Dipp } bonds. In stark contrast to the exclusive production of 2 , treatment of [( Me2 CAAC)CuAl{SiN Dipp }] ( 4 ), containing the more basic Me2 CAAC carbene ( Me2 CAAC = 1-(2,6-di-isopropylphenyl)-3,3,5,5-tetramethylpyrrolidin-2-ylidene), with phenylacetylene provided a mixture of several products, even at room temperature and irrespective of the reaction stoichiometry.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently described a family of molecules bearing unsupported group 11-aluminium bonds, in which the coinage metal centres are stabilised by various neutral donors, and the aluminium atom is supported by a six-membered diamide chelate. 13 In this contribution, therefore, we describe the reactivity arising from the copper alumanyl species, [{SiN Dipp }Al–Cu(NHC iPr )] (SiN Dipp = {CH 2 SiMe 2 NDipp} 2 ; Dipp = 2,6-di-isopropylphenyl; NHC iPr = N , N ′-di-isopropyl-4,5-dimethyl-2-ylidene), ( 1 ) and a variety of terminal alkynes. This chemistry provides an unusual alkyne-to-alkene transformation that may be viewed as an alkyne transfer semi-hydrogenation in which reduction is facilitated by the Cu–Al bond and in which the requisite protons are provided by the terminal alkyne itself (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The inherent reactivity of aluminyl anions rapidly opened new synthetic realizations and the formation of elusive Al–X bonds. , Coles et al reported the dimeric bis-amido Al­(I) complex II and its reaction with 1,3,5,7-cyclooctatriene (COT) displaying reduction and addition mechanisms . Hill and McMullin et al reported the seven-membered N,N′-heterocyclic potassium aluminyl III and its posterior reaction with alkaline earth compounds, Mg and Ca, to yield the corresponding Al–Mg and Al–Ca bonds .…”
Section: Introductionmentioning
confidence: 99%
“…alumanyl anions) continues to be hot topic in organometallic chemistry. 2 This is due both to fundamental interest, and also due to these nucleophilic anions allowing access to various aluminium-containing compounds that have been inaccessible via traditional routes. 2,3 Aluminyl anions are highly reactive species that are isoelectronic to carbenes when charge separated from their counterion.…”
mentioning
confidence: 99%
“…2 This is due both to fundamental interest, and also due to these nucleophilic anions allowing access to various aluminium-containing compounds that have been inaccessible via traditional routes. 2,3 Aluminyl anions are highly reactive species that are isoelectronic to carbenes when charge separated from their counterion. 2 This electronic structure opens the possibility of ambiphilic reactivity as the aluminium centre possesses both a lone pair of electrons and an empty p-orbital, but recent reports have been dominated by their reactivity as aluminium-centred nucleophiles.…”
mentioning
confidence: 99%